Uporaba kognitivne povratne zanke pri urjenju hoje s funkcionalno električno stimulacijo - Bajd, Tadej (Medicinski razgledi, 2005)
The rehabilitation system for re-learning of walking is aimed at gait trainingin patients with incomplete spinal cord injuries soon after the accident. It consists of three systems: actuation, sensory, and cognitive. Theactuation system is represented by afferent electrical stimulation. The sensory system makes use of goniometres, gyroscopes, accelerometers, foot-switches and computer vision. Cognitive information is delivered to the patient in the form of sensory electrical stimulation, and audio or visual feedback.
Keywords: Električna stimulacija, zdravljenje; Paraplegia; Hoja; Rehabilitation; Quadriplegia; Paraplegija; Gait; Tetraplegija; Povratna zveza; Electric Stimulation Therapy; Feedback; vocational rehabilitation; rehabilitacija; električna stimulacija